In-situ formation of Ge-rich SiGe alloy by electron beam evaporation and the effect of post deposition annealing on the energy band gap. (15th June 2018) - Tah, Twisha; Singh, Ch. Kishan; Amirthapandian, S.; Madapu, K.K.; Sagdeo, A.; Ilango, S.; Mathews, T.; Dash, S.
Abstract: We report the synthesis of polycrystalline ( poly )-SiGe alloy thin films through solid state reaction of Si/Ge multilayer thin films on Si and glass substrates at low temperature of 500 °C. The pristine thin film was deposited using electron beam evaporation with optimized in-situ substrate heating. Our results show the co-existence of amorphous Si ( a -Si) phase along with the poly -SiGe phase in the pristine thin film. The a -Si phase was found to subsume into the SiGe phase upon post deposition annealing in the temperature range from 600° to 800 °C. Additionally, dual energy band gaps could be observed in the optical properties of the annealed poly -SiGe thin films. The stoichiometric evolution of the pristine thin film and its subsequent effect on the band gap upon annealing are discussed on the basis of diffusion characteristics of Si in poly -SiGe.